2015
DOI: 10.1007/s00705-015-2727-1
|View full text |Cite
|
Sign up to set email alerts
|

Dengue hemorrhagic fever and the kidney

Abstract: Dengue virus infection (DVI)/dengue hemorrhagic fever (DHF) is a common febrile illness with a variety of severities. The mortality rate is high in dengue shock syndrome (DSS), caused by circulatory failure due to plasma leakage resulting in multi-organ failure. However, acute kidney injury (AKI) is rarely reported. In areas of endemic DVI, the prevalence of AKI due to DVI has been reported to be as high as 6.0 % in children with AKI, and 0.9 % in children with DVI who were admitted to a hospital. The mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
2
33
0
4
Order By: Relevance
“…Recent finding that uses epithelial cells as the target cells for dengue virus also satisfy to the previous research that reported the increase of porcine renal cell line LLC-PK1 when exposed to TNF-α, one of the cytokine that released by epithelial cells in response to dengue infection [14]. The evidence of the increase of the permeability of monkey kidney in response to dengue infection as found in the recent study may help to explain why the mortality of dengue patients with acute kidney injury was higher than those without kidney injury as reported by previous researchs [15,16,17].…”
Section: Discussionsupporting
confidence: 66%
“…Recent finding that uses epithelial cells as the target cells for dengue virus also satisfy to the previous research that reported the increase of porcine renal cell line LLC-PK1 when exposed to TNF-α, one of the cytokine that released by epithelial cells in response to dengue infection [14]. The evidence of the increase of the permeability of monkey kidney in response to dengue infection as found in the recent study may help to explain why the mortality of dengue patients with acute kidney injury was higher than those without kidney injury as reported by previous researchs [15,16,17].…”
Section: Discussionsupporting
confidence: 66%
“…Kidney involvement with dengue virus infection is being recognized, since the prevalence of proteinuria and hematuria has been reported as high as 70-80% [19]. Mechanisms that may drive kidney complications in dengue are not clear but possibly result from indirect pathways via host immunity.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, four fatal human cases that experienced the severe hemorrhagic symptoms of dengue had three of their peripheral sites (liver, lung and kidney) investigated. Organs were elected according to previous known relevance or knowledge gaps related to dengue [16–19, 23]. Research was focused on the cellular immunity, in which mononuclear cell migration and cytokine production were considered to the evaluation of host response by the fatal cases of severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Scarce current data show IgG, IgM, or C3 deposits with thickening of the glomerular basement membrane and hypertrophy of the mesangial cells in the areas with immune complex deposits, 19,20 which indicates that the damage can be because of a direct cytopathic effect of the viral protein on glomerular and tubular cells; by an immunological mechanism in situ, triggered by viral antigens linked to glomerular structures; or by injuries caused by inflammatory mediators released in response to glomerular and tubular cytopathic effects of viral antigens. 15,21 TMA associated with dengue is very rare and scarcely described;…”
Section: Discussionmentioning
confidence: 99%